Alter egos - Green, Laurence (Motion picture director); Copper Heart Entertainment; FeelSales (Canada : Copper Heart Entertainment, 2004)
A documentary about the life and work of the Canadian film animator Ryan Larkin (1943-2007), including a discussion with Larkin about Chris Landreth's Ryan, a 14-minute CGI animation.
"A Copper Heart Entertainment production in co-production with the National Film Board of Canada."
Originally released as a motion picture in 2004.
Felicity Fanjoy, Chris Landreth, Ryan Larkin, Tanya Tree, Robert Verrall.
Cinematographer, Jay Ferguson ; editor, Susan Martin.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 20, 2016).
Keywords: Larkin, Ryan, -- 1943-; Landreth, Chris; Animated films; Biographical films; Internet videos; Streaming video